Advances in management of the female athlete triad and eating disorders - Zach, K. N.; Smith Machin, A. L.; Hoch, A. Z. (Clinics in Sports Medicine, 2011)
Although there are numerous benefits to women from athletic participation, a complex combination of endocrine and metabolic factors exaggerates risk for a serious health concern: the female athlete triad. The purpose of this article is to provide updates on new issues related to the triad, specifically the relationship between athletic-associated amenorrhea and endothelial dysfunction—a potential fourth component to the triad that is a concern for future cardiovascular risk, public health issues, and athletic performance. Folic acid should be considered a potential safe and inexpensive therapeutic treatment to restore endothelial-dependent vasodilation.n